Strategy maps as a communication tool in balanced scorecard implementation: Study of a Malaysian utility company - Ayoup, Hazeline; Omar, Normah; Abdul Rahman, Ibrahim Kamal (2010)
This paper presents an exploratory and qualitative analysis of the Balanced Scorecard [BSC] implementation of a utility company in Malaysia.The use of strategy map as proposed under the BSC methodology in communicating company's strategic vision and mission from the corporate to the individual managerial level is explored.Although the BSC has been developed for almost 20 years, BSC implementation is still an issue.One of the underexplored issues is communication.It is critical for successful BSC implementation, but very little evidence is observed in the literature.Using qualitative research approach, this paper highlights a company experience in using the BSC strategy maps to facilitate strategy communication to managers.